Conscience at Stake - Paape Bud (Macmillan Nigeria Publishers Ltd, 1997)
The Nigerian civil war was just over and there were too many cases of armed robbery. It was the day of the first public execution in Ogoni. Father Darcy felt trapped as if in an endless forgotten purgatory. But the execution would not hold until he listened to a catholics confession. Events that followed took another turn, leading to Father Darcy's death.
Keywords: Juvenile Fiction / Realistic / Civil War